Development of a Climate Smart Financing Bundle for Tomatoes in Ghana - Wamicwe, Peter; Awuku Darko, Paa Kwesi; Heintz, Lennart; Derenoncourt, Marie Ena; Newman, Richard; Grosjean, Godefroy; Mufti, Samaa; Cosgrove, Bethany Emma; Koge, Jessica; Abera, Wuletawu; Mponela, Powell; Tahidu, Osman; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The report aims to provide an overview of the feasibility and pre-implementation phase activities being undertaken by AICCRA under The Aggregator Growth Development & Investment Program in Ghana to co-design a comprehensive scalable climate-smart bundled finance solution targeting the Tomato Value Chain.